Comparison between metabolites ant antioxidant activity of saffron (Crocus sativus L.) from Kashmar and Marand regions - Masoumeh Vakili-ghartavol (Zirā̒at va Fanāvarī-i Za̒farān, 2016)
Saffron (Crocus sativus L.) is a valuable product that is moderately resistant to drought and is cultivated in environments with very different climatic conditions. The most important chemical compositions of saffron include crocin and crocetin derivatives. Saffron is used as a food colouring and flavouring agent in the food industry. Moreover, it is utilized in folk medicine as antispasmodic, carminative, sedative, anti-depression and for heart disease. In this study, saffron samples from different altitudes, i.e. Marand with altitude of 1360m and Kashmar with altitude of 1000m above sea level were collected and dried in the same conditions and compared with commercial samples. Three major metabolites (crocin, picrocrocin and safranal) were quantified in both altitudes by Spectrophotometry. The results obtained showed that saffron samples from Marand had the most amounts of crocin and picrocrocin (absorbance: 306 and 118). Also, after extraction, antioxidant activity was quantified by the DPPH free radical scavenging method. The results indicated that saffron samples from Marand had higher concentration of these constituents and antioxidant activity in comparison to that of samples from Kashmar. However, due to reduction of rain and increasing drought in the Azerbaijan region, cultivation of saffron in Marand is recommended on the basis of the results of this research and high yield and quality of saffron.